A Preliminary Study of High-Field MRI Image Enhancement Techniques Applied to Low-Field MR Brain Images - N. F., Ishak; M. J., Gangeh; R., Logeswaran (SPRINGER, 2008)
Low-field Magnetic Resonance Imaging (MRI) is vital for sensitive surgery to allow real-time imaging in the operation theatre. In this paper, a short literature research on enhancing high-field MR brain images is presented. With the research, we demonstrate implementations of the algorithms in the literature on low-field MR brain images. A major concern in enhancing low-field MR brain images is the poor quality images secondary to a worsening signal-to-noise ratio (SNR) compared with the high-field MRI scanners. This paper gives some useful insight on the pros and cons of applying high-field MR image enhancement techniques on low-field MR brain images.